2022
DOI: 10.21834/ebpj.v7i20.3484
|View full text |Cite
|
Sign up to set email alerts
|

Men Health Seeking Behaviour: A literature review

Abstract: Gender equality between males and females is a Sustainable Development Goal (SDG) that the nation must address. However, compared to women, the health status of men lags. The objectives are to describe and summarize the factors influencing men's health-seeking behaviour in various health problems from published literature. Methods: The literature search was performed using online databases in Scopus, Web of Science and ScienceDirect. Findings: In a total of  22 studies that fulfilled the inclusion criteria, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The high CFRs among male cases is consistent with other studies that have demonstrated female sex as protective against unfavorable cholera outcomes [26,27]. This has been attributed to men seeking healthcare late and less often [28]. This study also concurred with previous observations of high cholera CFRs among children [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…The high CFRs among male cases is consistent with other studies that have demonstrated female sex as protective against unfavorable cholera outcomes [26,27]. This has been attributed to men seeking healthcare late and less often [28]. This study also concurred with previous observations of high cholera CFRs among children [29,30].…”
Section: Discussionsupporting
confidence: 91%